Etika: Keamanan Berpolitik dan Ber-New Media - Prajarto, Nunung (Jurnal Ilmu Sosial dan Ilmu Politik, 2011)
The improvement of security in politics and new media calls for fast action. Recent cases indicate that political position and rights to communication using new media cannot be guaranteed due to the problem of security. The reasons rest on the way the people get into politics and the aims they use new media. The following article explores how ethics may solve the problem of security, starting from ethics in democracy, politics, and new media, the causes of ethics violations, and attitudes for coping with security problems.